(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
To improve the sporophore qualities and creation yield of Pleurotus pulmonarius by interspecies hybridization between monokaryotic societies of P. pulmonarius and P. citrinopileatus, a sum of 100 potential pairings were finished. Five hybrids were gotten creating sporophores with morphological qualities predominant to those of P. pulmonarius. DNA investigation affirmed the high hereditary alliance of the hybrids with P. pulmonarius creating a bootstrap worth of 99. Among the hybrids, P19xC5 strain displayed great qualities, for example, higher mycelial development rate, thicker mycelium thickness just as producing sporophores with fleshier surface and greater pileus. Further investigation by producing showed that it had quicker development rate at 8.7 mmday instead of 8.2 and 7.7 mmday for P. pulmonarius and P. citrinopileatus, individually. It’s anything but a higher sporophores yield (182.97 g) and natural effectiveness (130.19) which was around doubles that of the parental strains.